Effect of compost with lechuguilla bagasse on Agave salmiana growth - Leal-Robles, Aida Isabel; Méndez-López, Alonso; Hidalgo De León, Aimir; P´´erez-Rivera, María Fernanda; Núñez-Colima, Juan Antonio (Ecosistemas y Recursos Agropecuarios, 2025)
Mexico is home of 75% of all agave species in the world. Agave salmiana has been used to prepare pulque, while Agave lechuguilla is used to make fibers, generating an unused residue (bagasse), several species are propagated through shoots, which makes them susceptible to their environment, as well as to pests and diseases. The aim of this study was to evaluate different substrates in the growth of A. salmiana. The study was developed at the Universidad Autonoma Agraria Antonio Narro in Saltillo, Coahuila, Mexico. It was established under a completely randomized experimental design with five repetitions for each treatment. The treatments (substrates) were peat Moss, manure with A. lechuguilla bagasse compost + peat Moss, and manure with A. lechuguilla bagasse compost. Rosette diameter, leaf length, root length, as well as fresh weight and dry weight at the end of the experiment were evaluated. A repeated measures analysis was performed over time, as well as an ANOVA for each sample of the variables mentioned above. The combination of A. Lechuguilla with manure compost with peat Moss was the treatment that generated the highest values of rosette diameter, leaf length, and fresh weight. Therefore, the use of compost based on lechuguilla agave with manure plus peat Moss favors the growth and development of A. salmiana seedlings.